Software Quality Modeling by Process - Rajasekhar Reddy, N; Vinaya Babu, M (International Journal of Computer Sciences and Engineering, 2025)
Our world runs on software. Every business depends on it, every mobile phone uses it, and even every new car relies on code. Without software, modern civilization would fall apart. Given this reality, the quality of that software really matters. Because it’s so widely used and so important, low-quality software just isn’t acceptable. But what exactly is software quality? It’s not an easy question to answer, since the concept means different things to different people. One useful way to think about the topic is to divide software quality into three aspects: functional quality, structural quality, and process quality. Doing this helps us see the big picture, and it also helps clarify the trade-offs that need to be made among competing goals.